The structural evolution of isolated galaxies at low redshift in the IllustrisTNG simulation. Issue 2 (24th March 2021) - Walters, Dan; Woo, Joanna; Ellison, Sara L; Hani, Maan H
ABSTRACT: We study the structural evolution of isolated star-forming (SF) galaxies in the IllustrisTNG100-1 hydrodynamical simulation, with a focus on investigating the growth of the central core density within 2 kpc (Σ*, 2 kpc ) in relation to total stellar mass ( M * ) at z < 0.5. First, we show that several observational trends in the Σ*, 2 kpc – M * plane are qualitatively reproduced in IllustrisTNG, including the distributions of active galactic nuclei (AGN), SF galaxies, quiescent galaxies, and radial profiles of stellar age, specific star formation rate (sSFR), and metallicity. We find that galaxies with dense cores evolve parallel to the Σ*, 2 kpc – M * relation, while galaxies with diffuse cores evolve along shallower trajectories. We investigate possible drivers of rapid growth in Σ*, 2 kpc compared to M * . Both the current sSFR gradient and the black hole (BH) accretion rate are indicators of past core growth, but are not predictors of future core growth. Major mergers (although rare in our sample; ∼10 per cent) cause steeper core growth, except for high-mass ($M_{\rm *}\gtrsim 10^{10} \, {\rm M}_{\odot }$ ) mergers, which are mostly dry. Disc instabilities, as measured by the fraction of mass with Toomre Q < 2, are not predictive of rapid core growth. Instead, rapid core growth results in more stable discs. The cumulative BH feedback history sets the maximum rate of core growth, preventing rapid growth in high-mass galaxies ($\gtrsim 10^{9.5} \, {\rm M}_{\odot }$ ). For massive galaxies, the total specific angular momentum of accreting gas is the most important predictor of future core growth. Our results suggest that the angular momentum of accreting gas controls the slope, width, and zero-point evolution of the Σ*, 2 kpc – M * relation.